The buffalo hunter hunter - Jones, Stephen Graham, 1972- (Saga Press, 2025)
"A chilling historical horror novel set in the American west in 1912 following a Lutheran priest who transcribes the life of a vampire who haunts the fields of the Blackfeet reservation looking for justice. A diary, written in 1912 by a Lutheran pastor is discovered within a wall. What it unveils is a slow massacre, a chain of events that go back to 217 Blackfeet dead in the snow. Told in transcribed interviews by a Blackfeet named Good Stab, who shares the narrative of his peculiar life over a series of confessional visits. This is an American Indian revenge story written by one of the new masters of horror, Stephen Graham Jones."--